Penulisan Artikel Ilmiah bagi Dosen STIQ ZAD - Wangsadanureja, Miftah; Saputra, Adha; Rabbani, Muhammad Aqil; Tsauri, Sidiq Samsi; Haris, Ahmad (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
Research and publication of scientific articles are core elements in academic development and quality improvement of higher education. Lecturers as the spearhead in the academic world have an important role in this process. Therefore, community service in the form of training in writing scientific articles for lecturers is an inevitable step to improve the capacity and quality of their research. This article discusses scientific article writing training for lecturers as one of the community service efforts in improving their research competence.